The ethics of right-mindedness-open morality- christianity - Dura, Adam A. (Folia Philosophica, 2002)
Each ethical system produces its morality: either open or closed, static or dynamic, and it leaves man less and less of free space. It happens that it demands from us only that our life should become fitted into a straitjacket of rules. The present article contains reflections on the open morality a possibility of which is included in J. Banka’s independent ethics, the ethics of right-mindedness. The problem is in fact much more complex because it is based on the assumption of the openness of this kind ethics towards other systems of moral philosophy, and, particularly, towards Christian ethics. The dynamic and open morality generated by the ethics of right-mindedness is crowned by the model of homo euthyphronicus. In this way, the modem man receives an independent and autonomous ethical system which, in exceptionally unfavourable conditions (connected with Post-modernism), allows us to keep our individuality and creative outlook on life.